A comunicação pública da ciência no Jornal UFG: análise de conteúdo e estudo de recepção - Steindorff, Kharen Stecca (2025)
For a long time, the dissemination of science to the general public has been studied with a focus on the sender, with a unidirectional approach to the message being sent. In contrast, authors such as Castelfranchi and Bueno proposed changes in science journalism, which mainly involved the area of the sociology of science. These changes highlighted the importance of integrating society into scientific production processes. Thus, this study sought to understand how the process of constructing the public communication of science occurs through the readership of Jornal UFG (a communication vehicle produced by the Secretariat of Communication (Secom) at the Federal University of Goiás). First, we listed some concepts already used to establish this interaction and advocated the use of the terminology "public communication of science” (PCS) in the development of our research. A bibliographic survey of these studies on PCS also helped us understand what characterizes this process. Next, we performed a content analysis of some articles in the Jornal, with the aim of finding elements of PCS. We then conducted empirical research to identify the profile of the vehicle's readership, using questionnaires, focus groups and interviews. Based on the samples collected from the target audience, we proposed possible contributions to increase the participation of the readership in the construction of public communication of science produced and disseminated by Jornal UFG.